Left atrial strain as sensitive marker of left ventricular diastolic dysfunction in heart failure. (2nd July 2020) - Frydas, Athanasios; Morris, Daniel A.; Belyavskiy, Evgeny; Radhakrishnan, Aravind‐Kumar; Kropf, Martin; Tadic, Marijana; Roessig, Lothar; Lam, Carolyn S.P.; Shah, Sanjiv J.; Solomon, Scott D.; Pieske, Burkert; Pieske‐Kraigher, Elisabeth
Abstract: Aims: The purpose of this retrospective analysis was to examine the association of left atrial (LA) strain (i.e. LA reservoir function) with left ventricular diastolic dysfunction (DD) in patients with heart failure with reduced and preserved left ventricular ejection fraction (LVEF). Methods and results: We analysed the baseline echocardiographic recordings of 300 patients in sinus rhythm from the SOCRATES‐PRESERVED and SOCRATES‐REDUCED studies. LA volume index was normal in 89 (29.7%), of whom 60.6% had an abnormal LA reservoir strain (i.e. ≤23%). In addition, the extent of LA strain impairment was significantly associated with the severity of DD according to the 2016 American Society of Echocardiography recommendations (DD grade I: LA strain 22.2 ± 6.6, rate of abnormal LA strain 62.9%; DD grade II: LA strain 16.6 ± 7.4, rate of abnormal LA strain 88.6%; DD grade III: LA strain 11.1 ± 5.4%, rate of abnormal LA strain 95.7%; all P  < 0.01). In line with these findings, LA strain had a good diagnostic performance to determine severe DD [area under the curve 0.83 (95% CI 0.77–0.88), cut‐off 14.1%, sensitivity 80%, specificity 77.8%], which was significantly better than for LA volume index, LA total emptying fraction, and the mitral E/e′ ratio. Conclusions: The findings of this analysis suggest that LA strain could be a useful parameter in the evaluation of DD in patients with heart failure and sinus rhythm, irrespective of LVEF.